Case reportTransverse myelitis in a patient with systemic lupus erythematosus – case report - Łukjanowicz, Małgorzata; Dąbrowska-Zimoń, Agnieszka; Ostanek, Lidia; Brzosko, Marek (Reumatologia/Rheumatology, 2006)
We report a case of a 20-year-old women diagnosed as systemic lupus erythematosus (SLE) with central nervous system involvement. She suffered from aseptic meningitis followed by transverse myelitis. The treatment with corticosteroids was complicated with acute pancreatitis. One year after the first episode of myelitis, exacerbation of SLE resulted in relapse of transverse myelitis. In this report we present a review of results of cerebrospinal fluid analysis and comparison of autoantibody titers in serum and cerebrospinal fluid.